Psycho-Social Aspects of Remote Work: The Results of Research Carried Out during the COVID-19 Pandemic - Mierzejewska, Katarzyna; Chomicki, Michał (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The aim of the article is to explore the psychosocial context of remote work. There is a particular focus on engagement and the inconvenience caused by a non-standard work format.Research Design & Methods: The study was conducted on a sample of 201 employees engaged in digital output and able work remotely.Findings: The study showed that non-remote workers exhibit greater vigour, dedication and absorption than those working remotely. The lack of social contact was recognised as the most significant drawback of remote work.Implications / Recommendations: Compared to standard work, long-term remote work can have a negative impact on individuals’ engagement in three dimensions – vigour, dedication and absorption.Contribution: The research results provide the basis for further exploration of psychosocial aspects of remote work.